Electrospun nanofibrous membranes incorporating an imidazole-appended p-phenylene-Cu(ii) ensemble as fluoroprobes for the detection of His-proteins1. Issue 36 (28th September 2015) - Kim, Ka Young; Jung, Sung Ho; Jung, Jong Hwa
<x xml:space="preserve">Abstract</x> Tetra-imidazole-appended p-phenylene-Cu(ii) doped nanofibrous membranes can function as "turn-on" portable fluorescence chemoprobes for Histidine.